A critical review and normalization of the life cycle assessment outcomes in the naval sector. Bibliometric analysis and characteristics of the studies. (15th October 2022) - Mio, Andrea; Fermeglia, Maurizio; Favi, Claudio
Abstract: Most of the actual industrial research efforts are aimed at reducing environmental burdens associated with human activities in the context of sustainable development. This trend has become increasingly prevalent in the naval transportation sector shown by a growing number of scientific publications dealing with life cycle assessments of maritime-related activities. However, the life cycle assessment framework provides practitioners with a variety of alternatives for conducting the analyses, giving room for defining key factors, such as functional units, system boundaries, and impact assessment methods, among others. This lack of standardization resulted in a wide range of assumptions and findings that are seldom comparable. The goal of this review is providing a systematic literature analysis, focusing on the characteristics of life cycle assessments dealing with the environmental impacts of various maritime vessel categories. In the first part, a qualitative analysis of the available scientific literature has been performed, providing a bibliometric analysis and a general overview of the characteristics of the studies ( i.e., life cycle impact assessment methodologies, background data, and software tools used). The outcomes of the bibliometric analysis are then summarized and discussed to understand current practices and future trends in this field, providing the basis for the normalization phase of the results. The second section of the paper offers advice for naval practitioners on how to perform results normalization to produce comparable analyses. Two approaches for normalization have been proposed in the frame of this study: an "horizontal" one, which is based on vessel features and allows a comparison among different vessel typologies, and a "vertical" one that enables to fairly compare vessels of the same category to one another. In addition, each section reports the outcomes of greenhouse gas-related impact categories, which have been subjected to the proposed normalization procedure, along with the order of magnitude of the results for each life cycle phase. The overall work provides an overview of LCA impact results as well as a collection of procedures and recommendations for future life cycle assessments based on specific vessel types, in terms of functional unit selection, system boundary definition, impact assessment approach, presentation of the outcomes, and normalization basis. Highlights: Bibliometric analysis highlights the general trends in LCA in the maritime sector. LCA outcomes of maritime vessels are normalized to gain comparable results. Normalization criteria are suggested based on the function and scope of the vessels. Efficiency Ratio assesses the operational performance regardless of the vessel category.